Integrating Islamic values and technological advancements in leadership and governance: A qualitative study of elementary school principals in Nigeria - Shu‘aib, Babamole, Murtadah; Dagbo, Yusuf Mashood (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2025)
This study explores how elementary school principals in Abuja, Nigeria, integrate Islamic leadership values and information and communication technology (ICT) in their leadership styles and governance practices. As educational institutions face increasing demands for ethical leadership and digital governance, this research examines how faith-based values and technological tools converge to shape school management. The study aimed to investigate two key areas: (1) the leadership styles of school principals informed by Islamic principles, and (2) the implementation of good governance through participatory and transparent practices supported by ICT. A qualitative multiple case study design was employed, involving 12 principals from Islamic-oriented elementary schools in Abuja. Data were collected through semi-structured interviews and non-participant observations, then analyzed thematically using a coding framework based on Islamic leadership theory, transformational leadership, and good governance models. Findings revealed that principals adopted a hybrid leadership model combining Islamic ethics, such as amanah (trust), adl (justice), and shura (consultation), with transformational leadership traits, including staff motivation and collaborative vision. ICT tools such as WhatsApp, Google Forms, and digital dashboards were used to enhance transparency, stakeholder engagement, and performance monitoring, all while reinforcing Islamic values of accountability and justice. The study concludes that effective educational leadership in Islamic contexts can be both spiritually grounded and technologically adaptive.